Are the Responses of Sectoral Energy Imports Asymmetric to Exchange Rate Volatilities in Pakistan? Evidence From Recent Foreign Exchange Regime - Saqib, Abdul; Chan, Tze-Haw; Mikhaylov, Alexey; Lean, Hooi Hooi (Frontiers in Energy Research, 2021)
Growing energy demand but stagnant production followed by volatile exchange rate leads Pakistan to energy imbalances and potential economic contraction. Yet, studies on sectoral energy imports are limited and inconclusive without accessing the asymmetric effect of currency fluctuations. We examine the impacts of Pakistani Rupee volatility on monthly energy imports based on the Nonlinear Autoregressive Distributed Lag (NARDL) estimations. Augmented Dickey Fuller and Phillip Peron tests were used to conduct unit root testing and bounds testing approach was used to examine the long-term cointegration. The long-run asymmetry is tested with Wald-test and using NARDL model we examined both short-run and long-run asymmetric effect of exchange rate volatility on energy imports. The bound test established and supported through 〖ECM〗_(t-1) (t-test), long-term cointegrating relationship between exchange rate volatility and energy imports. Among others, both short-run and long-run asymmetric effects were found for crude oil, coal, electricity and petroleum products. Rupee depreciation increased crude oil and electricity imports while the appreciation effects were insignificant. Overall, the empirical assessment reveals that foreign exchange volatility effect is sectoral specific and asymmetric in Pakistan. It offers new insights to re-strategize the energy policy and refining the import substitution plan.